DEVELOPING ENGLISH-OPOLY GAME AS A MEDIUM TO TEACH THE 8TH GRADERS SPEAKING RECOUNT TEXT (RETAIN, 2014)
DEVELOPING ENGLISH-OPOLY GAME AS A MEDIUM TO TEACH THE 8TH GRADERS SPEAKING RECOUNT TEXT Agnesia Gita Flamboyan English Department, Faculty of Languages and Arts, State University of Surabaya gita.flamboyan@yahoo.com Lies Amin Lestari English Department, Faculty of Languages and Arts, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Berbicara dianggap sebagai keterampilan yang paling sulit dalam belajar Bahasa Inggris. Observasi awal yang dilakukan di SMP 1 Ngoro menunjukkan bahwa para siswa mempunyai kemampuan yang baik dalam mengerti pelajara, namun mereka selalu ragu untuk berbicara. Para siswa membutuhkan suasana yang santai untuk belajar Bahasa Inggris di dalam kelas. Berbicara teks recount tidak bisa hanya dilakukan dengan mengerti struktur umumnya saja, tetapi juga perlu latihan untuk mengungkapkannya. Oleh karena itu, permainan modifikasi seperti English-opoly dibutuhkan sebagai media baru untuk membantu para siswa berbicara teks recount dengan cara yang menyenangkan. Karena permainan membuat suasana menyenangkan dan santai (Uberman, 1998). Penelitian ini menggunakan model R & D oleh Borg dan Gall untuk mengubah permainan monopoli biasa menjadi permainan bernama English-opoly yang digunakan untuk mengajar siswa kelas 8 berbicara teks recount. Selain itu, penelitian ini juga untuk mengetahui respon siswa terhadap permainan yang dikembangkan tersebut. Validasi ahlis menunjukkan bahwa game ini cocok untuk membantu siswa mencapai tujuan pembelajaran. Game ini juga memenuhi criteria sebagai permainan yang baik untuk digunakan sebagai media pembelajaran. Selanjutnya data dari observasi dan wawancara menunjukkan bahwa sebagian besar siswa memberikan respon yang baik dan setuju bahwa English-opoly bisa membantu mereka dalam belajar untuk berbicara teks recount. Kata Kunci: Berbicara, English-Opoly, Permainan, Siswa Kelas 8 Abstract Speaking is considered as the most difficult skill in learning English. An early observation done in SMPN 1 Ngoro showed that the students were good in understanding the lesson, but they were hesitant to speak. They needed more relaxing atmosphere in learning English in the classroom. Speaking recount text can not be measured by one’s knowledge on generic structure only, but it should also be measured by practicing to express it. Therefore modified game like English-opoly is needed as a new medium to help the students speak recount text easily in a fun way. Because games create fun and relaxing atmosphere (Uberman, 1998). This study used R & D model by Borg and Gall to develop the conventional monopoly game to become English-opoly for the teaching of speaking recount text to the eighth graders. Besides, this study also investigated the students’ responses toward the implementation of the game developed. The expert validation showed that the game is appropriate for the students to help develop objectives of the study. This game also fulfills the criteria of a good game as teaching medium. Furthermore, data from observation and interview showed that most of the students gave positive response and agree that English-opoly is helpful for them in learning speaking Recount text. Keywords: Speaking, English-opoly, Game, Recount Text, Eighth graders INTRODUCTION One of the hardest aspects for the teacher to help the students with is learning to talk in the foreign language HYPERLINK ł